Fabrication and Electrochemical Treatment Application of an Al-Doped PbO2 Electrode with High Oxidation Capability, Oxygen Evolution Potential and Reusability. Issue 10 (1st January 2015) - Xia, Yijing; Dai, Qizhou; Weng, Mili; Peng, Yue; Luo, Jinming; Meng, Xiaoyang; Luo, Xubiao; Chen, Jianmeng; Crittenden, John
Abstract : A novel Al-doped PbO2 electrode with high oxygen evolution potential and electrochemical oxidation performance is prepared by electrodeposition technique. The Al-doped PbO2 electrode has significant improvements in electrochemical oxidation ability and electrode stability. From the morphological point of view, the introduction of Al 3+ limits crystal particles and produces compact films. The films have better electrochemical oxidation ability and we demonstrated that by oxidizing aspirin. We found that the energy saving (using EE/O calculations) can be up to 34% after Al 3+ doping. Meanwhile, Al-doped PbO2 electrode showed higher reusability and stability than undoped PbO2 electrode.